Workers without Borders : Posted Work and Precarity in the EU - Wagner, Ines (Cornell University Press, 2018)
How the European Union handles posted workers is a growing issue for a region with borders that really are just lines on a map. A 2008 story, dissected in Ines Wagner's Workers without Borders, about the troubling working conditions of migrant meat and construction workers, exposed a distressing dichotomy: how could a country with such strong employers' associations and trade unions allow for the establishment and maintenance of such a precarious labor market segment?Wagner introduces an overlooked piece of the puzzle: re-regulatory politics at the workplace level. She interrogates the position of the posted worker in contemporary European labour markets and the implications of and regulations for this position in industrial relations, social policy and justice in Europe. Workers without Borders concentrates on how local actors implement European rules and opportunities to analyze the balance of power induced by the EU around policy issues.Wagner examines the particularities of posted worker dynamics at the workplace level, in German meatpacking facilities and on construction sites, to reveal the problems and promises of European Union governance as regulating social justice. Using a bottom-up approach through in-depth interviews with posted migrant workers and administrators involved in the posting process, Workers without Borders shows that strong labor-market regulation via independent collective bargaining institutions at the workplace level is crucial to effective labor rights in marginal workplaces. Wagner identifies structures of access and denial to labor rights for temporary intra-EU migrant workers and the problems contained within this system for the EU more broadly.